Implementasi Pendekatan Participatory Rural Appraisal pada Program Pelatihan - Ridwan, Ihwan; Dollo, Asdar; Andriyani, Andriyani (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study aims to determine the implementation of the rural appresial participatory approach in the women's empowerment program at PKBM Rezky Amaliyah and the empowerment model. This study uses a qualitative approach to PRA research design, research locations in the Masalle District, Enrekang Regency. data collection techniques using questionnaires, interviews and documentation. Research subjects are managers of PKBM, community leaders, partners and training participants. The technique used is purposive sampling, analysis the data used is quantitative descriptive analysis. The results showed that the PRA approach was effective in improving the standard of living of the community by utilizing information technology-based production houses. The PRA model formulated with PKBM managers found that at the reflection stage it was necessary to monitor and evaluate at the planning and action stages so that the outputs and outcomes of the activities could be known training.